INFLUENCE OF PH ON RELEASING PLATELET-DERIVED GROWTH FACTOR (PDGF-BB) FROM A Β-CHITOSAN-BASED HYDROGEL - Cabrel Rengifo, Sthefanie (2019)
A hydrogel with β-chitosan matrix that retards the release of platelet-derived growth factor - BB (PDGF - BB), which is part of the platelet lysate (LP) obtained from platelet rich plasma (PRP), was developed. The hydrogel was composed of a solution of 1.5 % (w/v) β-chitosan in 2 % (v/v) acetic acid, 6% or 12 % LP (v/v) and glutaraldehyde 0.03M. The β-chitosan used as raw material had 12.47 % of average relative humidity, 94.53 of average deacetylation degree and an estimated average molecular weight of 145.94 kDa; important attributes to formulate a hydrogel of semi-solid consistency, colorless and easy to handle. Delayed release was achieved with the 12 % LP hydrogel since the release of PDGF – BB does not differ significantly (p <0.05) by varying the pH from 6.5 (5 491.42 pg of PDGF – BB/mL of LP) to 7.4 (5 387.39 pg of PDGF – BB/mL of LP) after 32 hours. In contrast, the 6% LP hydrogel show a significant difference in the amount of PDGF-BB released by varying the pH from 6.5 (12 687.66 pg of PDGF – BB/mL of LP) to 7.4 (9 396.58 pg of PDGF – BB/mL of LP) after 32 hours.